Evaluation of oxygen extraction fraction in systemic lupus erythematosus patients using quantitative susceptibility mapping. Issue 8 (August 2019) - Miyata, Mari; Kakeda, Shingo; Kudo, Kohsuke; Iwata, Shigeru; Tanaka, Yoshiya; Wang, Yi; Korogi, Yukunori
The purposes of this study are to assess the oxygen extraction fraction (OEF) changes on MRI-based quantitative susceptibility mapping (QSM) in systemic lupus erythematosus (SLE) patients and to determine whether QSM-OEF is associated with disease activity in SLE. We enrolled 42 SLE patients and 20 healthy subjects (HS) who had no pathologies on conventional brain MRI. Disease activity was assessed using SLE Disease Activity Index (SLEDAI). For the measurement of QSM-OEF, QSM data were analysed using the Perfusion Mismatch Analyzer software program. Spearman's or Pearson's correlation coefficients were calculated, and independent predictors were identified through a multiple linear regression analysis. QSM-OEF was significantly higher in SLE than that in HS (51.3 ± 10.1 vs. 40.5 ± 3.7, p  < 0.001). QSM-OEF was positively correlated with SLEDAI and the presence of neuropsychiatric symptom (NPS) scores (ρ = 0.663, p  < 0.001 and ρ = 0.340, p  = 0.028). At multiple linear regression analysis, SLEDAI and NPS were independently associated with QSM-OEF (standardized β = 0.426, p  = 0.016 and standardized β = 6.148, p  = 0.029). In the SLE patients, QSM-OEF is associated with disease activity, which might predict an increased risk of stroke in SLE.